Evaluation of Sediment Quality Based on the Concentration of Heavy Metals Hg, Pb, Cd, Cu, Zn, and Ni in Jakarta Bay Using the Index Analysis Approach - Edward; T Triandiza; Abd Wahab Rajab; Safar Dody; MJ Rugebregt; Agus Kusnadi; RDA Opier (Geography, Earth Science and Environment: Research Highlights Vol. 6, 2025)
This study examines the distribution and contamination levels of heavy metals, including mercury (Hg), lead (Pb), cadmium (Cd), copper (Cu), zinc (Zn), and nickel (Ni), in sediment samples from Jakarta Bay. Five stations were analyzed at increasing distances from the coastline (0.5 to 20 km) to assess spatial variation. The results revealed significant contamination at Stations M (0.5 km) and D (5 km), where Hg, Pb, Cu, and Zn showed the highest concentrations, linked to industrial emissions and anthropogenic activities. Cadmium and nickel displayed moderate contamination levels, with more uniform distribution due to natural and industrial contributions. Contamination was quantified using the Contamination Factor (CF), Geo-Accumulation Index (Igeo), and Pollution Load Index (PLI). Stations M and D were classified as "moderately to heavily polluted," while Stations B (15 km) and A (20 km) exhibited lower contamination due to dilution and reduced anthropogenic input. Zinc showed the highest concentration among all metals, with a peak value of 441.91 µg.g-¹ at Station M. The study highlights the need for targeted remediation, stricter waste management regulations, and continuous monitoring to mitigate environmental and ecological risks. These findings provide a framework for sustainable sediment management and pollution control in Jakarta Bay.